Carcinogenicity of Poorly Soluble Low Toxicity Particles: Commentary on Epidemiology as a Risk Assessment “Reality Check” - Mundt, Kenneth A.; Santamaria, Annette B.; Thompson, William J.; Bates, Christopher A.; Boles, Corey; Dotson, G. Scott; Yong, Mei (Frontiers in Public Health, 2022)
Inhaled particles that are poorly soluble or insoluble and of low toxicity (“poorly soluble low toxicity” or “PSLT” particles), can accumulate in the lung and at lung overload levels induce lung cancers in rats. The question of whether PSLT particles increase lung cancer risk in humans is complicated by large differences between rats and humans and the relatively large particle doses administered in animal studies even when compared with heavy human occupational exposures. We review the findings of epidemiological studies on occupational exposure to each of three different PSLT particles (carbon black, talc and taconite). The epidemiological evidence indicates that at even very high occupational exposure levels at which non-malignant respiratory diseases including pneumoconiosis and even talcosis are observed, lung cancer risks appear not to be elevated. Although positive human cancer risks might be predicted based on extrapolation from overload doses in rats to relevant exposures in humans, the epidemiological “reality check” based on the three examples indicates that these PSLT particles are unlikely to increase lung cancer risk in humans even at high occupational levels of exposure. Therefore, we propose that careful evaluation of the epidemiological evidence can serve as a “reality check” for human risk assessment and help balance the risk evaluation process.